2020
DOI: 10.3390/ma13225124
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive-Oxidative Removal of Sulfides from Water by MnO2-Loaded Carboxylic Cation Exchangers

Abstract: Hybrid ion exchangers (HIX) containing manganese(IV) oxide (MnO2) based on macroporous and gel-type carboxylic cation exchangers as supporting materials were obtained. The hybrid materials were characterized using scanning electron microscopy with energy dispersive spectrometry (SEM/EDS), Fourier transform infrared spectroscopy (FTIR), X-ray powder diffraction (XRD) and nitrogen adsorption isotherms at 77 K and mercury porosimetry. HIX with introduced MnO2 (20.0–32.8 wt% Mn) were tested for removal of dissolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…9 compared the structural characteristics of several neutralizing materials. Montmorillonite shows IV type isotherm [19] and H3 type hysteresis loop [20] , which indicated that it has complex mesoporous structure and irregular pore structure. Shell powder, coral sand, calcite and dolomite showed I-type isotherm [21] , and there was no hysteresis loop, which indicated that they had the characteristics of microporous adsorbent [22] , and the saturated adsorption value was equal to the filling volume of micropores.…”
Section: Structural Advantagesmentioning
confidence: 99%
“…9 compared the structural characteristics of several neutralizing materials. Montmorillonite shows IV type isotherm [19] and H3 type hysteresis loop [20] , which indicated that it has complex mesoporous structure and irregular pore structure. Shell powder, coral sand, calcite and dolomite showed I-type isotherm [21] , and there was no hysteresis loop, which indicated that they had the characteristics of microporous adsorbent [22] , and the saturated adsorption value was equal to the filling volume of micropores.…”
Section: Structural Advantagesmentioning
confidence: 99%
“…Sulfides can be formed spontaneously by the anaerobic decomposition of sulfur-containing organic matter or the reduction of biological sulfates under the action of septic bacteria and sulfate-reducing bacteria, which usually occurs in natural systems such as marine, river and lake sediments as well as in the treatment of municipal and agricultural sewage and waste. 5 Moreover, the majority of manufactured dissolved sulfide and gaseous H 2 S pollutants are discharged into the natural environment. The average sulfide concentrations in wastewater from the petrochemical and leather industries are around 150 g L −1 and 360 mg L −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their form of porous spherical beads with mechanical strength and due to overcoming the propensity of parent nanoparticles to aggregate (by isolating them within the polymeric skeleton), HIXs are suitable for batch and flow-through systems, providing a highly accessible surface area, high sorption capacity, fast kinetics, and enhanced selectivity in purification processes (the Donnan membrane effect controls what type of ions can enter inside the resin structure) [ 11 ]. The different morphology of the host materials (ion exchanger macroreticular vs. gel-like structure), the diverse nature and concentration of the ionogenic functional groups (strongly or weakly acidic vs. strongly or weakly basic), the various methods of dispersing metal oxide NPs inside the polymer support, and the specific properties of immobilized metal oxide nanoparticles all contribute to the diversity of their applications, including separation processes, catalysis and biocidal actions [ 12 , 13 , 14 , 15 , 16 , 17 ]. The most popular HIXs are FeOOH, MnO 2 , and ZrO 2 doped anion exchangers.…”
Section: Introductionmentioning
confidence: 99%